2018
DOI: 10.1016/j.clinthera.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Efficacy of 0.1% Cyclosporin A Cationic Emulsion in Subjects with Severe Keratitis Due to Dry Eye Disease: A Nonrandomized, Open-label Extension of the SANSIKA Study

Abstract: Purpose: Results from a 6-month double-masked and a 6-month open-label study (SANSIKA) established the efficacy and safety of once-daily 0.1% cyclosporin A cationic emulsion (CsA CE) in severe keratitis due to dry eye disease (DED). This article presents results from the Post-SANSIKA study, a 24month extension of SANSIKA assessing the sustained efficacy of CsA CE after treatment discontinuation.Methods: Time to relapse (corneal fluorescein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 18 publications
3
22
0
2
Order By: Relevance
“…Исходные результаты теста Ширмера достоверно различались между группами пациентов, что, безусловно, было связано с особенностями Лечение хронического воспаления глазной поверхности представляет собой длительный процесс, в котором важна непрерывность и влияние на ключевые патофизиологические механизмы. Эффективность местного применения 0,1% катионной эмульсии циклоспорина А (Икервис) в лечении БСГ средней и тяжелой степени при болезни Шегрена была доказана в ранее проведенных, в том числе рандомизированных международных, исследованиях [6,11].…”
Section: практикующему врачуunclassified
See 1 more Smart Citation
“…Исходные результаты теста Ширмера достоверно различались между группами пациентов, что, безусловно, было связано с особенностями Лечение хронического воспаления глазной поверхности представляет собой длительный процесс, в котором важна непрерывность и влияние на ключевые патофизиологические механизмы. Эффективность местного применения 0,1% катионной эмульсии циклоспорина А (Икервис) в лечении БСГ средней и тяжелой степени при болезни Шегрена была доказана в ранее проведенных, в том числе рандомизированных международных, исследованиях [6,11].…”
Section: практикующему врачуunclassified
“…В последнее время в комплексном лечении БСГ применяют иммуносупрессанты (0,1% катионная эмульсия циклоспорина А). Циклоспорин А хорошо переносится пациентами, оказывает выраженное противовоспалительное действие при длительном лечении [6,10,11].…”
unclassified
“…ocular hypertension, cataracts and opportunistic infections) [ 4 , 29 ]. Multicenter, randomized controlled trials (RCTs) have demonstrated efficacy and safety outcomes with CsA 0.05% anionic solutions or 0.1% cationic emulsion (CE) treatment, with significant improvement observed concerning the signs and symptoms of DED [ 20 24 , 27 ]. In Europe, only CsA 0.1% CE is licensed for prescription and reimbursement [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is approved for the treatment of severe keratitis in adult patients with DED that has not improved despite treatment with tear substitutes [ 31 ]. Two double-masked, randomized, parallel-group, vehicle-controlled phase III studies, SICCANOVE and SANSIKA, examined treatment outcomes with CsA 0.1% CE in people with moderate-to-severe and severe DED, respectively [ 21 24 ]. In both studies, CsA 0.1% CE was well tolerated, reduced corneal surface damage and lowered ocular surface inflammation [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation